Pengaruh Kepemimpinan Kepala Sekolah Dan Sarana Prasarana Terhadap Kinerja Guru SMK Negeri Di Kota Prabumulih - Rika Yuseva; Nur Ahyani; Missriani, Missriani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
The purpose of this research is to know (1) the influence of the leadership of the school principal and the infrastructure jointly toward the teacher performance. (2) The influence of the school principal leadership and the infrastructure partially toward teacher performance. The research type of explanatory research using quantitative approach. The subject of this research is all the teachers from two units of public vocational high schools in Prabumulih city namely SMK Negeri 1 Prabumulih and SMK Negeri 2 Prabumulih numbered 45 respondents with the sample census technique. Data analysis methods using descriptive analysis and multiple linier regressions analysis compounds with the help of the program Statistical Package for the social sciences 22 (SPSS). The results of the study showed that the 1) is the influence of the school principal leadership and the infrastructure jointly toward teacher performance with the F test 29,620. This means that the school principal leadership and the infrastructure jointly synergized to realize of the teachers performance that are increasingly high. 2) There is a positive and significant impact the leadership of the school principal and the infrastructure partially toward teacher performance. That is a positive and significant impact on the school principal leadership toward teacher’s performance proved by the value of the t test 3,587. This means that the better the leadership of the school principal so that the teachers are also increasingly high performance. There is a positive and significant impact on the performance of the infrastructure of the teachers is proved by the value of the t test 2,801. This means that the more complete the infrastructure of schools and teacher performance will increase.